Real-World Methotrexate Dose on Clinical Effectiveness and Structural Damage of Certolizumab Pegol With Rheumatoid Arthritis - Nozaki, Yuji; Hidaka, Toshihiko; Ri, Jinhai; Itami, Tetsu; Tomita, Daisuke; Okada, Akinori; Ashida, Chisato; Ikeda, Fusayo; Yamamoto, Atsuhiro; Funahashi, Keiko; Kinoshita, Koji; Matsubara, Tsukasa; et al. (Frontiers in Medicine, 2021)
Objective: Rheumatoid arthritis (RA) treatments have markedly advanced with the introduction of biologic agents, e.g., tumor necrosis factor (TNF) inhibitors. TNF inhibitors are demonstrated to be quite effective in combination with methotrexate (MTX), and sufficient doses of both agents are important to control RA's disease activity. However, not all RA patients can be treated with high-dose MTX, due to contraindications related to the antimetabolite action of MTX or to tolerability concerns. In daily practice, this has resulted in reduced effectiveness of TNF inhibitors. We sought to determine whether the concomitant use of dose of MTX affected the clinical effectiveness, retention rate, and side effects of certolizumab pegol (CZP) for treating RA in a real-world setting. CZP is a pegylated-conjugated Fab' fragment of a humanized anti-TNF antibody that has high affinity to TNF. Patients and Methods: We divided Japanese RA patients treated with CZP (n=95, 25–83 years old) into groups based on those with (n=65) and without (n=30) concomitant MTX, and those treated with a high dose (≥8 mg, n=41) or low dose (1 to <8 mg, n=24) of MTX. We retrospectively analyzed the concomitant MTX doses' effects and side effects, and the patient retention rate. Results: There were no significant differences among the CZP groups with and without In review 3 MTX or the groups receiving the high vs. low MTX doses in the retention rate, the low disease activity rate, or the inhibitory effect in radiographic joint damage. Conclusion: CZP has the potential to be a useful biological agent to control RA's disease activity and the bone destruction in patients who cannot tolerate a sufficient MTX dose.